Desfecho de 42 mil casos de SARS-CoV-2 em um município do estado de Mato Grosso : papel dos sintomas no desfecho - Lima, Gessica Fernanda Colnago de (2023)
INTRODUCTION: The coronavirus disease 2019 (COVID-19) pandemic is a major public health problem worldwide with high rates of morbidity and mortality. Elderly patients or patients with comorbidities are more likely to develop more severe conditions and consequently have a high rate of hospital lethality. The presence of some symptoms in SARS-CoV-2 infection can be associated with lower rates of mortality and admission to the ICU in patients. The aim of this study was to determine the associations between the clinical characteristics and clinical outcomes of SARS-CoV-2 infection patients. METHODS: This was a retrospective cohort study of patients with COVID-19 in 2020– 2021 in a municipality in the Midwest region of Brazil. The variables analyzed were age, sex, clinical characteristics, clinical results and presence of comorbidities in patients. Associations between the clinical or epidemiological characteristics were analyzed using appropriate tests for categorical variables and continuous normal or parametric distributions. An alpha value of 5% was used as the maximum error limit allowed to reject the null hypothesis in all analysis. RESULTS: In total, 42,469 patients were analyzed, with lethality rates of 4.4% and 2.9% in 2020 and 2021, respectively. There was a higher mortality in men (p = 0.000), the elderly (p = 0.000), patients with dyspnea (p = 0.000), or patients with comorbidities (p = 0.000). The presence of headache, sore throat, anosmia, dysgeusia or diarrhea were related with a lower mortality (p = 0.000). MAIN CONCLUSIONS: This study demonstrated higher lethality, revealing a higher mortality rate in patients who were male, aged over 65 years, with dyspnea, or with comorbidities. However, headache, sore throat, anosmia, dysgeusia, or diarrhea were associated with an improved prognosis. Further studies to elucidate these findings are warranted.